Controlling or Channeling Demands? How Schedule Control Influences the Link Between Job Pressure and the Work-Family Interface. Issue 3 (August 2021) - Badawy, Philip J.; Schieman, Scott
Schedule control is theorized as a job resource that should reduce the extent to which work demands bleed into nonwork time and decrease work-to-family conflict. However, schedule control might also come with greater expectations that workers fully devote themselves to work even during non-conventional work times; in this scenario, schedule control might act as a channel through which job demands can more easily permeate nonwork roles and generate conflict. Drawing on four waves of panel data from the Canadian Work, Stress, and Health Study (2011–2017), the authors use fixed effects regression techniques to discover some contradictions in the resource functions of schedule control. The authors find that schedule control exacerbates the effect of job pressure on role blurring, and these observed downsides of schedule control are stronger for women. By discovering gendered effects in the moderating role of schedule control, this study sharpens prevailing knowledge about its functions as a resource and the ways that it might channel stressful work-related demands.